Напружено-деформований стан і розрахунки за деформаційною методикою елементів з деревини при дії одноразових та повторних навантажень - Гомон, Святослав Степанович (Національний університет водного господарства та природокористування, 2020)
Запропоновано теоретично та експериментально обґрунтовану теорію деформування елементів з цільної та клеєної деревини за стиску, розтягу, прямого та косого поперечного згину при дії одноразових та повторних навантажень. Доведено, що для розрахункового перерізу зі складкою можна застосовувати відомі закони розподілення деформацій по висоті, як в стиснутій, так і в розтягнутій зонах, які обумовлюється гіпотезою суцільності і однорідності матеріалу. Встановлено існування стадій напружено-деформованого стану елементів з деревини з наявністю утворення складок в стиснутій зоні, розроблено аналітичний апарат і запропоновано деформаційну методику визначення напружено-деформованого стану нормальних перерізів дерев’яних елементів, що зазнають поперечного згину. Обґрунтовано пропозиції щодо вибору критеріїв вичерпання несучої здатності елементів з деревини виходячи з доведеної трансформації фізичного стану в механічний. Предложено теоретически и експериментально обоснованную теорию деформирования элементов из цельной и клееной древесины при сжатии, растяжении прямом и косом поперечном изгибе при действии однократных и повторных нагрузок. Доказано, что для расчетного сечения со складкой можно применять известные законы распределения деформаций по высоте, как в сжатой, так и в растянутой зоне, которые обуславливается гипотезой сплошности и однородности материала. Установлено существование стадий напряженно-деформированного состояния элементов из древесины с наличием образования складок в сжатой зоне, разработан аналитический аппарат и предложено деформационный метод определения напряженно-деформированного состояния нормальных сечений деревянных элементов, испытывающих поперечный изгиб. Обоснованы предложения по выбору критериев исчерпания несущей способности элементов из древесины исходя из доказанной трансформации физического состояния в механический. The introduction substantiates the relevance, purpose and objectives of research, the general characteristics and scientific novelty, the practical value of the work. The first section provides an overview of the features of loading elements from wood, the stages of the theory of the development of deformation and resistance to force action of wood. A thorough analysis of the current state of experimental and theoretical research and existing methods for testing elements of wood is presented. On the basis of the inspection, the directions of scientific research and the ways of solving the tasks set in the thesis are indicated. The second section is devoted to experimental and theoretical studies of the diagrams of the mechanical state of wood under the action of a one-time short-term longitudinal compression, stretching, chipping, as well as in nailed and glued joints. The developed equipment and experimental research methods made it possible to obtain complete diagrams of longitudinal compression of wood. An analysis of the results of experimental studies and an analytical description of the mechanical state of solid and glued wood during a single short-term deformation along the fibers in the hard load application mode to complete failure is performed. The main characteristic sections and parameters of the mechanical state of wood under compression - tension along the fibers, as well as the state of deformation of the wood under short-term, long-term, repeated, constant and episodic loading are established. The third section presents the results of experimental-theoretical studies of the mechanical state diagrams of solid and glued wood at various work cycles under the action of low-cycle loads. The features of the work of wood under various modes of repeated loads during longitudinal compression, of wood fibers adjacent to the plane of longitudinal cleaving and adjacent to the plane of adhesive joints are highlighted. Methods have been developed for determining the low-cycle adaptation of wood and its endurance in glued and nailed joints. The results of experimental studies of the operation of nailed joints from dry and wet wood and wood in the holes of these compounds under the influence of low-cycle loads are presented. The fourth section is devoted to experimental and theoretical studies of the operation of wood elements in direct and oblique transverse bending. A study of the basic deformative characteristics of wood under longitudinal compression and lateral bending was carried out, and a new method was proposed for determining the elastic modulus on samples of structural dimensions. The laws of determining the layer-by-layer deformation of solid and glued wood by the height of the normal section of the bending element at various levels and load conditions are established. A technique is proposed for determining the neutral cross-section line and patterns of change in its position under the action of single and low-cycle loads are shown. The critical and limiting values of the relative deformations under the longitudinal action of loads are established. In the fifth section, working hypotheses and prerequisites for modeling the stress-strain state of the normal section of solid and glued wood elements are proposed. A design apparatus for determining the bearing capacity of wood elements and criteria for its loss have been developed. In the calculations, the normal calculated cross section is taken to be the portion of the bending element made of wood, where a fold is formed in the compressed zone at the stage of work before fracture, since the section with the fold is a weak section. In the calculations, the apparatus of infinitesimal quantities was used, since the condition of continuity of the function in the vicinity of the section point is fulfilled, and in solid mechanics it is determined by the hypothesis of continuity and homogeneity of the material. The possibility of transforming physical state diagrams into diagrams of the mechanical state of wood elements is substantiated, the concept of the stages of work of wood structures under load is proposed for the first time. The sixth section is devoted to the determination of the stress-strain state of normal sections of solid and glued wood elements with direct and oblique bending at different stages of operation under the influence of short-term single and low-cycle loads. And their detailed analysis was performed. The seventh section sets out the main provisions of the calculating method for the strength of normal design sections of wood elements in transverse bending based on the deformation model. A mathematical apparatus has been developed for calculating normal sections of solid and glued wood beams under the action of single and repeated loads when working in conditions of direct and oblique transverse bending. A technique for predicting the performance of wood structures under repeated loads is proposed.
Напряженно-деформированное состояние и расчет по деформационной методике элементов с древесины при действии одноразовых и повторных нагрузок
Stress-strain state and calculations according to the deformational method of wood elements under single and repeated loads
Keywords: wood elements; stiffness; state diagrams; critical deformations; work stages; estimated section; fracture criteria; bearing capacity; 624. 011:620.172/.178.2